Experimental Study of Pedagogical Conditions for the Use of National Traditions in the Harmonious Upbringing of the Personality of Preschoolers - Ulguzi, Eshonkulova (European Journal of Life Safety and Stability (2660-9630), 2023)
in this article, an attempt was made to study by experience the pedagogical conditions for the use of national customs in the harmonious upbringing of the personality of preschoolers and, in addition, an attempt was made to highlight the content of the article using national customs.